(untitled) (The Pakistan Development Review, 1985)
In the pursuit of social justice, the problem of relative economic inequality in developing countries deserves serious consideration. With the help of a formal analytical framework, the present paper shows that the essential elements of a solution of the problem are structural change, focusing on narrowing down the difference in initial wealth holdings, and an active ’incrementalist’ policy of keeping the growth rate of the income of the poor significantly higher than the growth rate of the income of the rich. Naive egalitarianism, requiring only the equality of these two growth rates in the name of moderation, will only create an explosive situation in which economic inequality will keep on increasing. It is further argued that in the context of solving the problem the critical points are the ones where the income and wealth gaps begin to narrow down. Once these points are reached, relative inequality will be finally eliminated in a fairly short time regardless of the relative size of the initial wealth holdings. Policy action to achieve the stated objective will require a marriage of structural change and incrementalism rather than an emphasis on one to the neglect of the other.